Phenolic Compound Profiles in Grape Skins of Cabernet Sauvignon, Merlot, Syrah and Marselan Cultivated in the Shacheng Area (China) - Shi, P.B.; Yue, T.X.; Ai, L.L.; Cheng, Y.F.; Meng, J.F.; Li, M.H.; Zhang, Z.W. (South African Journal of Enology and Viticulture, 2016)
The phenolic compounds in the grape skins of Cabernet Sauvignon (CS), Merlot (ML), Syrah (SY) and Marselan (MS) from Shacheng, in China, were compared using HPLC-MS/MS. The results showed that the types and levels of phenolic compounds varied greatly with cultivars. Malvidin derivatives were the main anthocyanins. CS and ML showed a higher content of malvidin-3-O-(6-O-acetyl)-glucoside than malvidin-3-O-(trans-6-O- coumaryl)-glucoside, while SY and MS differed from CS and ML. ML had higher delphinidin and cyanidin derivatives, SY had higher peonidin derivatives, while malvidin and petunidin were higher in MS. The total content of flavonols, flavan-3-ols, phenolic acids and stilbenes in grape skins showed no difference among CS, ML and MS. Isorhamnetin-3-O-glucoside (CS, ML, MY), quercetin-3O-glucoside (SY), procyanidin trimer (SY, MS), procyanidin dimer (CS, ML), syringetin-3-O-glucoside, trans-cinnamic acid and resveratrol were the most abundant non-anthocyanin phenolic compounds. Cluster analysis showed that CS and ML, and SY and MS had similar phenolic profiles.